Penilaian Rumah Sehat pada Rumah di Kelurahan Batu Bersurat - Adeswastoto, Hanantatur; Desrimon, Arfi; Lelis Febrianty, Nanda (Journal of Social and Community Service, 2025)
This community service activity aims to assess healthy homes in Batu Bersurat Village, Kampar Regency, Riau. The background to this activity is the problem of inadequate sanitation, limited access to clean water, and low public awareness of the importance of environmental health. The implementation method of the activity includes field surveys, data collection, processing of assessment results, and socialization to the community about the concept of healthy homes in accordance with the Technical Guidelines for Healthy Home Assessment from the Directorate General of Disease Control and Environmental Health, Ministry of Health of the Republic of Indonesia (2007). The assessment is carried out using a score weighting system, where a house is categorized as healthy if it obtains a score of 80–100% of the total maximum score of 1280. The results of the activity indicate that some houses do not meet healthy home standards due to limited sanitation and ventilation facilities, and the continued presence of waterlogging problems. Through this program, the community gains practical knowledge about home hygiene, rainwater management through the construction of infiltration wells, and the implementation of clean and healthy living behaviors. This activity is expected to improve the quality of environmental health, reduce the risk of disease, and become a model for implementing healthy home assessments in other areas.